Influence of Group on Individual Subject Maps in SPM Voxel Based Morphometry - Michael, Andrew M.; Evans, Eli; Moore, Gregory J. (Frontiers in Neuroscience, 2016)
Voxel based morphometry (VBM) is a widely utilized neuroimaging technique for spatially normalizing brain structural MRI (sMRI) onto a common template. The DARTEL technique of VBM takes into account the spatial intensity distribution of sMRIs to construct a study specific group template. The group template is then used to create final individual normalized tissue maps (FINTM) for each subject in the group. In this study we investigate the effect of group on FINTM, i.e., we evaluate the variability of a constant subject’s FINTM when other subjects in the group are iteratively changed. We examine this variability under the following scenarios: (1) when the demographics and conditions for the iterative groups are similar, (2) when the average age of the iterative groups is increased and (3) when the number of subjects with a brain disorder (here we use subjects with autism) is increased. Our results show that when subject demographics of the group remains similar the mean standard deviation (SD) of FINTM gray matter (GM) of the constant subject was around 0.01. As the average age of the group is increased, mean SD of GM increased to around 0.03 and at certain brain locations variability was as high as 0.23. A similar increase of variability was observed when the number of autism subjects in the group was increased where mean SD was around 0.02. Further, we find that autism versus control GM differences are in the range of -0.05 to +0.05 for more than 97% of the voxels and note that the magnitude of the differences are comparable to GM variability. Finally, we report that opting not to modulate during normalization or increasing the size of the smoothing kernel can decrease FINTM variability but at the loss of subject-specific features. Based on the findings of this study we outline precautions that should be considered by investigators to reduce the impact of group on FINTM and thereby to derive meaningful group differences when comparing two cohorts of subjects.